Microbial population heterogeneity versus bioreactor heterogeneity: Evaluation of Redox Sensor Green as an exogenous metabolic biosensor. Issue 7 (16th August 2016) - Baert, Jonathan; Delepierre, Anissa; Telek, Samuel; Fickers, Patrick; Toye, Dominique; Delamotte, Anne; Lara, Alvaro R.; Jaén, Karim E.; Gosset, Guillermo; Jensen, Peter R.; Delvigne, Frank
Abstract : Microbial heterogeneity in metabolic performances has attracted a lot of attention, considering its potential impact on industrial bioprocesses. However, little is known about the impact of extracellular perturbations (i.e. bioreactor heterogeneity) on cell‐to‐cell variability in metabolic performances (i.e. microbial population heterogeneity). In this work, we have evaluated the relevance of Redox Sensor Green (RSG) as an exogenous biosensor of metabolic activity at the single‐cell level. RSG signal is proportional to the activity of the electron transport chain and its signal is strongly affected by metabolic burden, availability of electron final acceptor, and side metabolisms (i.e. overflow and mixed acid fermentation). RSG can also be used for the estimation of the impact of scale‐down conditions on microbial metabolic robustness. The relationship linking averaged RSG activity and its cell‐to‐cell variability (noise) has been highlighted but seems unaffected by environmental perturbations.